Tribes, Government and History in Yemen - William C. Young (International Institute of Islamic Thought, 1997)
This book is complex and, at points, obscure. Yet it is also an exceptionally rich collection of information about trihal identity and ethos in Yemen and, for scholars with a special interest in Yemeni society, can be a valuable resource. The author orients much of his material toward two main questions, neither of which I formulated explicitly: How can tribal political organization and state legal institutions co-exist, not only for brief moments but for over 1,000 years? and How have the names and boundaries of tribal territories been preserved with little change for such a long time? The answer to the first question is on p. 165: " ... the hijrah [in Yemeni Arabic: a protected space or person] provided the point around which both states of the world turned: strong Imams fheads of state] and weak. It could do so because it meant different things to different people.” The first 150 pages of the book, especially chapters 2 (“The Language of Honour”), 3 (“Tribes and Collective Action”) and 4 (“Estates of Society within the Tribal Peace”), lead up to and persuaded us to accept the conclusion that the mutual recognition by the state and by the tribes of neutral zones and people in tribal territories facilitated trade, tribe-state communication, and contact between literate Islamic specialists and illiterate farmers and stock-breeders. Even when the interests of the tribes and the state were directly opposed (for instance, in controlling roads and determining rates of taxation), violent conflicts between tribe and state were kept partly in check by tribal custom, just as they were when tribe clashed with tribe (see pp. 267, 268, 379-387) ...